KRITIK IBRAHIM M. ABU RABI’ ATAS PERSEPSI ISLAMOFOBIA BARAT - Almas, Afiq Fikri (UIN Sunan Kalijaga Yogyakarta, 2024)
Islamophobia symptoms significantly emerged among Westerners after the attack on the World Trade Center in the United States on September 11, 2001. Furthermore, the gap between the ideals of Islam as a religion of peace and the Western perception of Islam as a violent religion has become an issue that needs addressing. This research employs a qualitative method based on literature sources, focusing on the thoughts of Ibrahim M. Abu Rabi’, who proposes an approach in religious studies to correct Islamophobia. The research is conducted through literature sources, documents, archives, and similar materials. Ibrahim M. Abu Rabi’ emphasizes the importance of studying Islam through historical and sociological religious approaches. Through the